One day at a time: living with frailty: implications for the practice of advance care planning: a multiple case study - Bramley, Louise (2016)
Background: Advance care planning (ACP) was originally designed to promote autonomy and is commonly conceptualised as informing treatment and decisions in the event of a person’s loss of capacity. In the UK, healthcare policy has emphasised the potential for ACP to significantly contribute to improvements in experiences of death and dying for patients and their significant others. Older people with progressive frailty are at high risk of mortality, loss of capacity and increasing dependency on carers and care services, yet uptake of ACP in this group is poor. Little is known about whether frail older people regard advance care planning as relevant or what perspectives they have on decision making for the future.